2010
DOI: 10.1186/1475-2891-9-42
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and herbal supplements for anxiety and anxiety-related disorders: systematic review

Abstract: BackgroundOver the past several decades, complementary and alternative medications have increasingly become a part of everyday treatment. With the rising cost of prescription medications and their production of unwanted side effects, patients are exploring herbal and other natural remedies for the management and treatment of psychological conditions. Psychological disorders are one of the most frequent conditions seen by clinicians, and often require a long-term regimen of prescription medications. Approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(78 citation statements)
references
References 64 publications
2
69
1
6
Order By: Relevance
“…edulis . Passifl ora was listed as offi cial plant drug in the 1970s and 1990s by the pharmacopoeias of America, Britain, Germany, France, Switzerland, Egypt and India (Lakhan & Vieira, 2010;Fiebich et al, 2011;Sarris et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…edulis . Passifl ora was listed as offi cial plant drug in the 1970s and 1990s by the pharmacopoeias of America, Britain, Germany, France, Switzerland, Egypt and India (Lakhan & Vieira, 2010;Fiebich et al, 2011;Sarris et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Необ-ходимо выделить 3 фитотерапевтических агента, наи-более исследованных и широко применямых в неврологии: валериану лекарственную (Valeriana officinalis L.), мяту перечную (Mentha piperita L.) и ме-лиссу лекарственную (Melissa officinalis L.) [9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: оригинальные исследованияunclassified
“…Plants that are most studied with anxiolytic potential are Kawa, the St. John's Wort and Passiflora spp. [4][5][6][7]. The Passiflora extract has been used in many researches, presenting in their chemical constitution polyphenols, polyunsaturated fatty acids, fiber and other substances, such as passiflorin, one indole alkaloid, being the last one associated with anxiolytic effects [3].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of Passiflora incarnata L on anxiety was previously assessed in animals [8,4] and in humans [9][10] with satisfactory results [7]. Epidemiological studies have shown that the fear of public speaking is one of the biggest phobias that affect people, being highly prevalent among students [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation